Stress and coping strategies in public speaking: comparative case studies of Japanese and Malaysian undergraduates / Ameiruel Azwan Ab Aziz … [et al.] - Ab Aziz, Ameiruel Azwan; Anuar Yatim, Ariff Imran; Nordin, Nor Afifa; Norwahi, Nur Aqilah (Akademi Pengajian Bahasa, 2021)
Public speaking competency is one of the core skills that is essential for personal and professional growth. Students who display effective public speaking skills are able to get their messages across while projecting confidence, clarity and conviction which enhance their job prospects for future employability. Conversely, students' failure to cope with stress faced in preparing for public speaking may affect their speaking effectiveness. The comparative case studies aimed to explore the stress and coping strategies faced in public speaking among Japanese and Malaysian undergraduate students in two universities to understand the similarities, differences and patterns across these two groups that share a common focus. Study participants were selected through purposive sampling technique in which relevant data was collected using semi-structured interviews. Data gathered were then analysed thematically to identify the stressors and coping strategies in public speaking across the two groups. Results indicate similar stressors experienced by participants which are external speech stress factors, resource deficit and anticipatory speech anxiety in public speaking. Personal, social and academic oriented strategies were the participants’ strategies to cope with the stress. These findings suggest that similar stressors are faced by undergraduate students in performing public speaking, as well as and coping strategies used. This shows that the stress of public speaking is a prevalent occurrence and that institutional intervention can be developed by tertiary institutions to minimise its detrimental effects.